PREVALENCE OF INTESTINAL PARASITES IN FOOD HANDLERS TREATED IN THE MUNICIPALITY OF LIMA, PERU - Villegas, Wignard (2012)
The aim of this study was to determine the prevalence of intestinal parasites in food handlers that attended the Metropolitan Municipality of Lima, Peru. A total of 217 stool samples were examined between July and August, 2011. Direct methods were used with Lugol, or centrifugation technique Ritchie formalin-ethyl acetate as concentration method and Ziehl-Neelsen modified for detection of coccidia. Of the total sample, 107 (49.3%) were males and 110 (50.7%) were females. The average age of the study population was 26.78 years-old. The overall prevalence of parasites was 71.89%. There was no statistically significant differences in the prevalence of parasitism in terms of gender and age of the study population. The higher prevalence of intestinal parasites was found in the age group of 18-27 years (46.1%). The most prevalent species of protozoa were: Blastocystis hominis (55.8%), Entamoeba coli (30.9%), Endolimax nana (20.7%), Chilomastix mesnili (5.5%) and Giardia intestinalis (5.1%). The helminths found were: Hymenolepis nana (3.7%), Necator americanus/Ancylostoma duodenale (2.3%), Strongyloides stercoralis (1.8%), Trichuris trichiura (1.4%), Diphyllobothrium sp. (0.5%), Enterobius vermicularis (0.5%) and Trichostrongylus sp. (0.5%). Monoparasitism predominated (33.64%) and between parasitic associations, biparasitism was more frequent (21.2%). The beta diversity index of similarity Kulczynski -1 showed that the protozoa are more related to each other and likewise each other helminths. Ritchie technique showed higher efficiency than the direct method in the diagnosis of protozoan cysts.